A study on survivors of acute myocardial infarction developing transient ischemia on Holter monitoring - jalali, Tariq; Goyal, Vikas (International Journal of Medical Research and Review, 2015)
Introduction: Increasing array of medical intervention available to modify the likelihood of developing recurrent episode of myocardial ischemia, it is important to identify patients of risk of provocable myocardial ischemia before discharge. Material Methods: longitudinal study carried out in a tertiary care hospital of central India, over a period of one year. During the monitoring period, the patient was once subjected for 100-meter brisk walk. Result: Out of 64 cases, 6 (9.5%) cases developed ischemia during Holter, in male it was 5(10.2%) while in female it was 1(6.67%). 6.3% of total cases suffered from sustained VT during hospitalization.42.5% of cases of anterior wall myocardial infarction were presented with sinus tachycardia, it was found to be statistically significant(x2 = 73.55, p<0.001). Conclusion: After acute myocardial infarction, pre-discharge Holter monitoring (including brisk walk) is a good non-invasive method to detect ischemia in high risk patients.